1997
DOI: 10.1021/jp971934l
|View full text |Cite
|
Sign up to set email alerts
|

NEXAFS Spectroscopic Study of Organic Photographic Dyes and Their Adsorbed States on AgCl and AgBr

Abstract: The near-edge X-ray absorption fine structure (NEXAFS) spectra were studied at the S K-edge using synchrotron radiation for various sulfur-containing organic photographic materials in the solid state and in the adsorbed states on AgCl and AgBr grains. The features in the spectra of neat solids were assigned by mutual comparison and polarization dependence. The spectra of merocyanine dyes containing thiocarbonyl group were drastically affected by the adsorption on AgCl and AgBr, with significant suppression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Among these categories of dyes, the cyanine, merocyanine, and squaraine dyes are substances with a variety of colors but are not widely used for dyeing purpose, as they are decolorized by light and acid. They have, however, for example, been employed extensively as spectral sensitizers for silver halide photography and other inorganic large band-gap semiconductor materials, in optical disks as recording media, in industrial paints, for trapping of solar energy, as laser materials, in light-harvesting systems of photosynthesis, as photorefractive materials, as antitumor agents, and as probes for biological systems. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these categories of dyes, the cyanine, merocyanine, and squaraine dyes are substances with a variety of colors but are not widely used for dyeing purpose, as they are decolorized by light and acid. They have, however, for example, been employed extensively as spectral sensitizers for silver halide photography and other inorganic large band-gap semiconductor materials, in optical disks as recording media, in industrial paints, for trapping of solar energy, as laser materials, in light-harvesting systems of photosynthesis, as photorefractive materials, as antitumor agents, and as probes for biological systems. …”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Among these categories of dyes, the cyanine, merocyanine, and squaraine dyes are substances with a variety of colors but are not widely used for dyeing purpose, as they are decolorized by light and acid. They have, however, for example, been employed extensively as spectral sensitizers for silver halide photography and other inorganic large band-gap semiconductor materials, [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] in optical disks as recording media, [25][26][27] in industrial paints, for trapping of solar energy, 28 as laser materials, [29][30][31][32] in lightharvesting systems of photosynthesis, [33][34][35] as photorefractive materials, 5 as antitumor agents, 36 and as probes for biological systems. [37][38][39][40][41] This review concerns work on cyanines and merocyanines carried out during the 1990s related to their self-organization, nonlinear optical (NLO) properties, photodimerization, photoisomerization, solvatochromic behavior, behavior in organized system, and use as fluorescent sensors.…”
Section: Introductionmentioning
confidence: 99%
“…Since this process is strongly influenced by the crystal structure, researchers' efforts have been directed to control crystal size and shape in order to increase the photographic resolution, light sensitivity, and chemical stability. Moreover, through the absorption of suitable organic molecules at the silver halide crystal surface, it is possible to widen the sensitivity range to the whole visible spectrum, thus increasing both black-and-white and color photography performances. …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, through the absorption of suitable organic molecules at the silver halide crystal surface, it is possible to widen the sensitivity range to the whole visible spectrum, thus increasing both black-andwhite and color photography performances. [4][5][6][7] On the other hand, if suitable conditions to avoid photodecomposition are found, silver halide nanoparticles can also have important applications in heterogeneous catalysis. Calzaferri et al in 1996 8 found that, under UV irradiation, AgCl supported on SnO 2 in the presence of a small excess of Ag + and dispersed in aqueous solution is able to catalyze photooxidation of water.…”
Section: Introductionmentioning
confidence: 99%
“…Merocyanine dyes (Shindy et al, 2012;Shindy et al, 2016;Shindy et al, 2008) have found wide application in various areas of science and technology. They are used as optical sensors, spectral sensitizers for silver halide photography (Peng et al, 1996;Chen et al, 1995;Araki et al, 1997), and recording medium in optical disks. Their potential application as photosensitizers for photodynamic therapy (PDT) (Gomer et al, 1991; Krieg et al, 1993;Redmond et al, 1994) and radiation sensitizers for solid tumor treatment (Harriman et al, 1991) has been extensively studied.…”
Section: Introductionmentioning
confidence: 99%